THE ROLE OF BIG DATA ANALYSIS IN FINANCIAL DECISION MAKING: THE CASE OF ISLAMIC BANKING - Gunawan Widjaja (Jurnal Ekonomi dan Bisnis, 2024)
The use of big data from a Islamic economic perspective is certainly an important issue and cannot be postponed any longer, because the disparity in big data between the real sector and the financial sector, which has so far resulted in a lack of completeness in assessments, can be overcome by the limited data provided through big data. It is also possible that various matrices and cluster variants will emerge for various business sectors in an ecosystem. So it will make it easier to determine supply and demand in an ecosystem system. In this way, a closed loop economy based on a sharia ecosystem will be built automatically when big data is formed. This research uses an exploratory descriptive approach by analyzing the role of big data analysis in financial decision making: the case of Islamic banking. This scientific work was also developed using a literature review or library study approach. This research discusses the basic concepts of big data analysis consisting of the definition and characteristics of big data, financial decision making in sharia banking, and the potential application of big data analysis in Islamic banking.